Gastroesophageal reflux evaluation in patients affected by chronic cough: Restech versus multichannel intraluminal impedance/pH metry1. (28th September 2012) - Ummarino, Dario; Vandermeulen, Liv; Roosens, Bart; Urbain, Daniel; Hauser, Bruno; Vandenplas, Yvan
Abstract: Objectives/Hypothesis: : Oropharyngeal (OP) pH monitoring has been developed to detect supra‐esophageal gastric reflux (SEGR). The results obtained with OP pH‐metry and multichannel intraluminal impedance/pH monitoring (MII/pH) were compared. Study Design: : Diagnostic study. Methods: : Ten patients (age 46.33 ± 9.86 years) presenting with chronic coughing underwent simultaneous OP and MII/pH recording. A 2‐minute interval was allowed between events detected with both techniques to be considered simultaneous. Results: : A total of 515 reflux episodes were recorded with MII/pH (acid: 181; weakly acid: 310; weakly alkaline: 24); 180 (35%) reached the highest impedance channel (hypo‐pharynx); 74/180 (41%) were not related to a change in pH, according to the antimony electrode of the MII/pH catheter located at the upper esophageal sphincter. The OP monitoring measured 39 acid events; 17 (43.6%) were swallows according to MII, and 15 (38.5%) were not associated with MII or pH change. Only seven episodes were detected simultaneously with both techniques (1.3% for MII vs. 18% for OP; P = 0.0002). We found 49 pH‐only refluxes at the pH sensor in the hypo‐pharynx with MII/pH; only three (6.1%) correlated with OP reflux. Correlation in time between cough and reflux events was positive in 5/10 patients for MII (symptom index 5/10, symptom association probability 4/10), but in 0/10 patients according to OP pH metry. Conclusion: : OP pH metry detected less reflux episodes than MII/pH; 35% of the OP events were swallows according to impedance. Time correlation between cough and reflux could not be demonstrated with OP pH metry.